Kleveta svobode, diskriminacija dostojanstva - Jeršič, Alja (Analiza (Ljubljana), 2025)
In contemporary Western liberalism, freedom of expression is often elevated to a fundamental value that is supposed to protect the plurality of opinions and the autonomy of each individual. However, in the context of pornography, this ideal becomes entangled in its own contradictory web, where freedom of expression threatens to become a means of reinforcing inequality. This article problematizes the liberal understanding of such freedom, which, in the name of tolerance, often overlooks the power relations that condition this discourse. In the first part of the article, we present R. Dworkin's understanding of freedom as uncoerced choice and C. A. MacKinnon's feminist critique, which argues that pornography is not only freedom of expression but also a discourse in which freedom of expression turns into freedom of oppression. In the second part, we argue that liberal tolerance of content that degrades (especially female) bodies reveals the paradox of tolerance, which loses itself in fear of censorship. In conclusion, we emphasize that freedom without ethical responsibility does not liberate, but discriminates.
Keywords: capitalism; feminist philosophy; feministična filozofija; kapitalizem; liberalism; liberalizem; pornografija; pornography; Svoboda